Unprecedented cleavage of -N-N- bond of ligand and phenyl ring nitration during nitric oxide (NO) reactivity studies: new ruthenium nitrosyl complex and photoinduced liberation of NO. Issue 19 (17th December 2022) - Ratnam, Anand; Kumari, Sheela; Singh, Sain; Mawai, Kiran; Kumar, Rajan; Singh, U. P.; Ghosh, Kaushik
Abstract: A two-step procedure was used to make the ruthenium nitrosyl complex [Ru(L 3 )(PPh3 )(NO)Cl2 ] (1a) . The product generated when ligand L 1 and [Ru(PPh3 )3 Cl2 ] reacted to an acidified nitrite solution treatment. Single-crystal X-ray diffraction was used to determine the crystal structure of (1a) . Complex (1a) has a Ru–NO 6 moiety in the Enemark–Feltham notation and was found to be diamagnetic in nature. Photolytic cleavage of metal-bound NO in (1a) was observed under ultraviolet light, and photoreleased free NO was trapped by reduced myoglobin. The amount of photoreleased NO was estimated by the Griess assay. DFT computations were also performed to authenticate the electronic properties of (1a) . UF0001